Molecular cloning, biochemical characterization, and differential expression of an acetyl-CoA C-acetyltransferase gene (AACT) of brahmi (Bacopa monniera) - Vishwakarma, Rishi K.; Ruby; Singh, Somesh; Sonawane, Prashant D.; Srivastava, Sameer; Kumari, Uma; Kumar, R. J. Santosh; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Bacopa monniera (Brahmi) is an important Indian medicinal herb found in wet damp and marshy places. It produces medicinally important compounds known as bacosides along with alkaloids like brahmine and herpestine. Bacosides are triterpenoid saponins and their biosynthesis takes place via the isoprenoid pathway starting with acetyl-CoA. Acetyl-CoA C-acetyltransferase (AACT; EC 2.3.1.9), also known as acetoacetyl-CoA thiolase (Thiolase II), catalyzes the condensation of two acetyl-CoA to form 4-C compound acetoacetyl-CoA. Acetoacetyl-CoA is an important starting molecule for biosynthesis of various metabolites. Here, we report the cDNA cloning and characterization of acetyl-CoA C-acetyltransferase gene from B. monniera. The full-length gene was isolated using a RACE PCR protocol. The cDNA encoding AACT was designated as BmAACT (FJ947159) revealed an ORF of 1,218 bp and 405 amino acids, and shares 80 % similarity with other plant AACTs. Phylogenetic analysis showed that BmAACT is related closely to other dicot plants AACTs. The BmAACT gene was over-expressed in Escherichia coli as a 6X His-tag fusion protein and purified to homogeneity by Ni-NTA and gel filtration chromatography. Activity of recombinant protein was confirmed by thiolytic cleavage of acetoacetyl-CoA in the presence of 5 mM Mg2+, showing K (m) and V (max) of 20.67 mu M and 96.21 mu mol/min, respectively, with high catalytic efficiency (k (cat) = 2.30 x 10(5) min(-1)). Quantitative real-time PCR analysis showed that the expression of BmAACT is tissue-specific, and accumulation of transcripts is greater in roots and petals, followed by sepals, stem, leaf and pedicel.
Keywords: Acetyl-CoA C-acetyltransferase; Bacopa monniera; Isoprenoid pathway; Triterpenoid saponin